2018
DOI: 10.1002/ird.2298
|View full text |Cite
|
Sign up to set email alerts
|

Performance Assessment of Water Delivery and Distribution in Som Kamla Amba Irrigation Scheme

Abstract: The objective of this study was to assess the water delivery performance of the Som Kamla Amba irrigation scheme located in the Dungarpur district of Rajasthan using adequacy, equity and dependability indicators. Three minors each at the head, mid and tail sections of main canals (Right and Left Main Canal) and branch canals (Aspur Branch Canal and Baroda Branch Canal) were selected. The ratio of water delivered (obtained from discharge measured at outlets) and water required (calculated from CROPWAT software)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 11 publications
0
1
0
Order By: Relevance
“…It was found that Results were good (1.00 to 0.93), fair (0.84 to 0.80) and poor (0.42 to 0.18) adequacy at the head, mid and tail sections of each canal respectively and poor equity in water delivery as its value varied from 0.35 to 0.92. The Dependability was found to be good at head, fair at mid and poor at tail sections [1].…”
Section: Introduction Conomy Of Pakistan Is Based On Agriculturesmentioning
confidence: 91%
“…It was found that Results were good (1.00 to 0.93), fair (0.84 to 0.80) and poor (0.42 to 0.18) adequacy at the head, mid and tail sections of each canal respectively and poor equity in water delivery as its value varied from 0.35 to 0.92. The Dependability was found to be good at head, fair at mid and poor at tail sections [1].…”
Section: Introduction Conomy Of Pakistan Is Based On Agriculturesmentioning
confidence: 91%